2020
DOI: 10.1128/mbio.01242-20
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Analysis of Trypanosoma cruzi Persistence Foci at Single-Cell Resolution

Abstract: Infections with Trypanosoma cruzi are usually lifelong despite generating a strong adaptive immune response. Identifying the sites of parasite persistence is therefore crucial to understanding how T. cruzi avoids immune-mediated destruction. However, this is a major technical challenge, because the parasite burden during chronic infections is extremely low. Here, we describe an integrated approach involving comprehensive tissue processing, ex vivo imaging, and confocal microscopy, which allowed us to visualize… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
89
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(94 citation statements)
references
References 40 publications
5
89
0
Order By: Relevance
“…Infection with Trypanosoma cruzi (T. cruzi), the etiological agent of Chagas disease, triggers both innate (1)(2)(3), and adaptive (4)(5)(6) immune responses that aim at the control of the parasite load both in tissues and peripheral blood [Reviewed in (7)]. However, these mechanisms do not succeed in the complete eradication of the parasite, which results in parasite persistence (8)(9)(10)(11)(12).…”
Section: Introductionmentioning
confidence: 99%
“…Infection with Trypanosoma cruzi (T. cruzi), the etiological agent of Chagas disease, triggers both innate (1)(2)(3), and adaptive (4)(5)(6) immune responses that aim at the control of the parasite load both in tissues and peripheral blood [Reviewed in (7)]. However, these mechanisms do not succeed in the complete eradication of the parasite, which results in parasite persistence (8)(9)(10)(11)(12).…”
Section: Introductionmentioning
confidence: 99%
“…(B) Percentage of parasites that were EdU+ve under each treatment regimen. Colonic tissue was extracted from mice post-mortem , 18 hours after the second injection (1-day treatment) or 4 hours after the final injection (3.5-days treatment), and infected cells detected by ex vivo imaging and confocal microscopy (Materials and methods) (Figure 3 – figure supplement 1) (Ward et al . 2020).…”
Section: Resultsmentioning
confidence: 99%
“…2014; Costa et al . 2018; Ward et al . 2020), we demonstrated that the gastrointestinal tract, specifically the colon and stomach, is a key site of T. cruzi persistence during chronic murine infections.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations